Sustainable tourism as a solution to mitigate the negative impacts of tourism: A case study of Dubai - ELMILOUDI Souaad; FOUKA fatima; HARIRI Abdelghani (Journal of North African Economies, 2025)
This research paper aims to highlight the role of sustainable tourism in avoiding and mitigating the negative impacts of tourism. This sector, which is growing faster than all other economic sectors, has established significant importance for most countries around the world due to its positive effects, including improving the balance of payments, alleviating poverty, and reducing unemployment rates, especially in economies focusing on development. However, on the other hand, many negative aspects have emerged that negatively affect the economies of tourist countries. This paper sheds light on the case of Dubai, where tourism is a major economic resource but has suffered from the effects of the COVID-19 pandemic and the country's lockdown. Sustainable tourism, with its elements, is considered one of the most important solutions to alleviate these effects.